20.28.3 problem 3

Internal problem ID [4065]
Book : Differential equations and linear algebra, Stephen W. Goode and Scott A Annin. Fourth edition, 2015
Section : Chapter 11, Series Solutions to Linear Differential Equations. Additional problems. Section 11.7. page 788
Problem number : 3
Date solved : Monday, January 27, 2025 at 08:07:23 AM
CAS classification : [[_2nd_order, _exact, _linear, _homogeneous]]

\begin{align*} \left (-x^{2}+1\right ) y^{\prime \prime }-6 x y^{\prime }-4 y&=0 \end{align*}

Using series method with expansion around

\begin{align*} 0 \end{align*}

Solution by Maple

Time used: 0.002 (sec). Leaf size: 39

Order:=6; 
dsolve((1-x^2)*diff(y(x),x$2)-6*x*diff(y(x),x)-4*y(x)=0,y(x),type='series',x=0);
 
\[ y \left (x \right ) = \left (3 x^{4}+2 x^{2}+1\right ) y \left (0\right )+\left (x +\frac {5}{3} x^{3}+\frac {7}{3} x^{5}\right ) D\left (y \right )\left (0\right )+O\left (x^{6}\right ) \]

Solution by Mathematica

Time used: 0.002 (sec). Leaf size: 38

AsymptoticDSolveValue[(1-x^2)*D[y[x],{x,2}]-6*x*D[y[x],x]-4*y[x]==0,y[x],{x,0,"6"-1}]
 
\[ y(x)\to c_2 \left (\frac {7 x^5}{3}+\frac {5 x^3}{3}+x\right )+c_1 \left (3 x^4+2 x^2+1\right ) \]